2018
DOI: 10.1029/2017gb005855
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Asymmetry in the Evolution of Surface Ocean pCO2 and pH Thermodynamic Drivers and the Influence on Sea‐Air CO2 Flux

Abstract: It has become clear that anthropogenic carbon invasion into the surface ocean drives changes in the seasonal cycles of carbon dioxide partial pressure (pCO2) and pH. However, it is not yet known whether the resulting sea‐air CO2 fluxes are symmetric in their seasonal expression. Here we consider a novel application of observational constraints and modeling inferences to test the hypothesis that changes in the ocean's Revelle factor facilitate a seasonally asymmetric response in pCO2 and the sea‐air CO2 flux. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 102 publications
9
71
0
Order By: Relevance
“…No attempt has been made to correct for this bias in this present work, although we note that this bias is primarily an issue for surface measurements and this analysis focuses on the ocean interior. We nevertheless note that previous studies (e.g., Fassbender et al, 2018 ;Landschützer et al, 2018 ;Lenton et al, 2012) have indicated that there is a nonnegligible difference between summertime and wintertime trends in surface ocean pCO 2 , and it is possible that this is also the case for pH. Therefore, the anthropogenic CO 2 impacts on pH (and Ω) estimated here, which align with previous estimates (e.g., Caldeira & Wickett, 2003), should be considered representative of the summertime.…”
Section: Datasupporting
confidence: 88%
See 1 more Smart Citation
“…No attempt has been made to correct for this bias in this present work, although we note that this bias is primarily an issue for surface measurements and this analysis focuses on the ocean interior. We nevertheless note that previous studies (e.g., Fassbender et al, 2018 ;Landschützer et al, 2018 ;Lenton et al, 2012) have indicated that there is a nonnegligible difference between summertime and wintertime trends in surface ocean pCO 2 , and it is possible that this is also the case for pH. Therefore, the anthropogenic CO 2 impacts on pH (and Ω) estimated here, which align with previous estimates (e.g., Caldeira & Wickett, 2003), should be considered representative of the summertime.…”
Section: Datasupporting
confidence: 88%
“…Therefore, the anthropogenic CO 2 impacts on pH (and Ω) estimated here, which align with previous estimates (e.g., Caldeira & Wickett, ), should be considered representative of the summertime. Relatedly, warming of the ocean also affects the amplitude of the seasonal cycling and ocean stratification, which has been shown to affect ocean p CO 2 (Fassbender et al, ; Landschützer et al, ). The same effect is likely for ocean acidification, but the GLODAPv2 data product, due to the seasonal bias, cannot be used to assess this effect.…”
Section: Methodsmentioning
confidence: 99%
“…To account for correlation between ALK and DIC and strong dilution with freshwater (e.g., Fassbender et al, ) at inner harbor sampling stations, we use freshwater mixing (∆Ω mix ) and biogeochemical (∆Ω BGC ) terms rather than ∆Ω DIC and ∆Ω ALK , as has been done in a number of other studies (e.g., Doney, Lima et al, for pCO 2 ; Wang et al, ; Xu et al, for Ω) or a combined biophysical term (e.g., Fassbender et al, for pCO 2 ). The mixing term reflects the effects on Ω of changes of DIC and ALK as a function of salinity for two‐endmember conservative mixing determined for Buzzards Bay: ∆Ωmix=f(),,,normalT0normalS0DICnormalSALKnormalSΩ0, …”
Section: Methodsmentioning
confidence: 99%
“…This means that the temperature component of pH does not grow in constant proportion to the annual mean value, while pCO 2 does. The result is that when viewed as pH, in some areas the amplitude of pH decreases over time, but when viewed as [H + ] the amplitude increases (Fassbender et al, , figure 5). The cause of this apparent discrepancy is that the log scale of pH conceals the magnitude of the change in [H + ], giving the impression that the changes are smaller than they actually are.…”
mentioning
confidence: 99%
“…Separating and attributing different drivers to carbon system changes will not necessarily be easy, but it will be important. Fassbender et al () make a great contribution to helping us better understand seasonal changes in the marine carbon cycle.…”
mentioning
confidence: 99%